2010
DOI: 10.1183/09031936.00149109
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies induced with recombinant VP1 from human rhinovirus exhibit cross-neutralisation

Abstract: Human rhinoviruses (HRVs) are the major cause of the common cold and account for 30-50% of all acute respiratory illnesses. Although HRV infections are usually harmless and invade only the upper respiratory tract, several studies demonstrate that HRV is involved in the exacerbation of asthma.VP1 is one of the surface-exposed proteins of the viral capsid that is important for the binding of rhinoviruses to the corresponding receptors on human cells. Here we investigated its potential usefulness for vaccination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
83
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(86 citation statements)
references
References 46 publications
(62 reference statements)
1
83
0
Order By: Relevance
“…It is likely that the 39 kDa band common to each RV preparation is VP1 since it has been shown previously to migrate at this molecular weight (Skern et al, 1987). To confirm the presence of antibodies against VP1 in sera from mice infected twice with RV1B we performed ELISA using purified recombinant VP1 from RV serotypes RV14 and RV89 (Edlmayr et al, 2011) as the antigen since recombinant VP1 from RV1B was unavailable. We observed that mouse IgG2a from RV1B infected animals bound to the more similar VP1 from RV89 (66% identity between RV1B and RV89 VP1) but not to VP1 from RV14 (43% identity between RV1B and RV14 VP1) (Fig.…”
Section: Rv Capsid Protein Vp1 Is a Major Antibody Targetmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that the 39 kDa band common to each RV preparation is VP1 since it has been shown previously to migrate at this molecular weight (Skern et al, 1987). To confirm the presence of antibodies against VP1 in sera from mice infected twice with RV1B we performed ELISA using purified recombinant VP1 from RV serotypes RV14 and RV89 (Edlmayr et al, 2011) as the antigen since recombinant VP1 from RV1B was unavailable. We observed that mouse IgG2a from RV1B infected animals bound to the more similar VP1 from RV89 (66% identity between RV1B and RV89 VP1) but not to VP1 from RV14 (43% identity between RV1B and RV14 VP1) (Fig.…”
Section: Rv Capsid Protein Vp1 Is a Major Antibody Targetmentioning
confidence: 99%
“…RV preparations were inactivated by exposing them to UV light (1,200 mJ/cm2 for 30 min) as previously described (Bartlett et al, 2008). Recombinant VP1 from RV14 and RV89 was expressed and purified as described (Edlmayr et al, 2009(Edlmayr et al, , 2011.…”
Section: Rhinovirus Preparationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that immunization of rabbits with recombinant VP1 generates antisera with broad cross-serotype neutralizing properties [13] and VP1 is the dominant target of Abs in both humans [12] and mice [11] following RV infection. VP1 is the central and most external of the RV capsid proteins, contains receptor binding sites for both the major and minor group RV [40], and has a high degree of amino acid identity within both type A and B RV serotypes [41,42].…”
Section: Antibody Responses To Rhinoviruses and Neutralizing Epitopesmentioning
confidence: 99%
“…Nevertheless, several Abs (approximately 10 of 200) are undergoing preclinical development or are in clinical trials for viral infectious diseases targets including HIV-1, HBV, human rhinoviruses (RV) and human cytomegalovirus [3]. RV may be particularly suited to the application of prophylactic Abs as no appropriate antiviral therapies are available despite numerous attempts [5][6][7], vaccine development faces challenging obstacles [8,9] and new information regarding protective antibody responses is being unearthed [10][11][12][13][14]. Thus, a full evaluation of the application of prophylactic Abs to these important human pathogens where there is an explicit need for appropriate therapeutic/ prophylactic interventions is warranted.…”
mentioning
confidence: 99%